“No other weapon except organization”: The Métis Association of Alberta and the 1938 Metis Population Betterment Act - O’Byrne, Nicole (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2013)
In the 1930s, the Métis Association of Alberta (MAA) successfully lobbied the provincial government to establish a royal commission to inquire into the socio-economic conditions affecting the Métis living in Alberta. The MAA strongly advocated that land be set aside so that the Métis could continue to pursue their traditional economic livelihoods of hunting, trapping, and fishing. Following the recommendation of the Ewing Commission, the provincial government passed the 1938 Metis Population Betterment Act, which provided for Métis land settlements. These lands represent the first time in Canadian history that a provincial government set aside land in response to Métis claims. The MAA and provincial government both agreed on the land grant, but for different reasons. The Métis were motivated by historical claims to redress failed government policies such as the Métis scrip program and to protect land rights from the further incursion of non-Aboriginal settlement. By contrast, the provincial government saw the land grant as an expedient and inexpensive way to distribute relief to one of the province’s poorest populations. This paper illuminates the Alberta government’s response to the political lobbying efforts of the MAA in the 1930s to address the question of why Alberta was the first (and only) Canadian province to set aside Métis land settlements.